MARKETING INTELLIGENCE AND ITS ROLE IN CUSTOMER HAPPINESS WITHIN PROJECTS EVALUATION CRITERIA-ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF THE ASIA CELL COMPANY EMPLOYEES-HOLY KARBALA BRANCH - Dr. Sanaa Jasim Mohammed; Dejla Jasim Mohammed; Ali Abdulhussaein Khaleel Alfadhel (Scholars Digest Publishing, 2023)
The study aims to know and measure the relationship between the marketing intelligence system in customer happiness, As part of the criteria for evaluating existing investment projects, as it is the main basis for obtaining marketing information that provides organizations in formulating the appropriate marketing strategy for them. . The study adopted the analytical approach as a methodology for the study, and this study was applied to a sample of employees of Asia Cell Company - Holy Karbala Branch, who were randomly selected by submitting a questionnaire prepared for this purpose, and 70 individuals participated in this questionnaire. The most prominent statistical tools used are confirmatory factor analysis, correlation coefficient, simple and multiple regression coefficient, and path analysis. The main and sub-hypotheses were tested by using the ready-made statistical program (SPSS.V.20 and Amos.v.20) to process the data. The study reached a number of results that Asiacell uses an integrated system of marketing intelligence to support its orientation in customer happiness in order to achieve competitive advantages among Between them, it was found that there is a significant effect of marketing intelligence on customer happiness. The study recommends increasing the interest of the management of the Asiacell company under study in all factors that lead to customer happiness.
Keywords: marketing intelligence, customer happiness.